HYPERTENSION AS A SILENT KILLER DISEASE: EDUCATION FOR AT-RISK COMMUNITIES IN PEKUWON VILLAGE - Zethira, Andini Tania; Hendrati, Lucia; Diyanah, Khuliyah; Pawitra, Aditya; Jasmine, Meuthia; Syahputri, Remit; Alvionita, Annisa; Khaerati, Mutmainah; Bratajaya, Kusuma; Prabasanti, Mezaluna; Suryanegara, Elang; Rahayu, Az-Zahra; Liviansyah, Nabilla; Arif, Muhammad; Siregar, Fitri (Universitas Airlangga, 2024)
Hypertension is often called a silent killer disease because it does not give symptoms to the affected person. Bojonegoro Regency in East Java is one of the areas with a high rate of non-communicable diseases, reaching 385,465 people. Pekuwon Village in Bojonegoro Regency is one of many areas with high hypertension problems. An education program is needed to increase knowledge about hypertension as a disease that can come unexpectedly. The target of this education program is the people of Pekuwon Village aged 15-59 years. The hypertension education program was carried out during the Posbindu PTM activity in Pekuwon Village which was attended by 39 participants. The speaker of the education program was a village cadre who had been trained by the community service team of the Faculty of Public Health, Universitas Airlangga. The evaluation used pre-test before giving information and post-test after giving information. The results showed an increase in knowledge from 63.63% to 97.43%. These results meet the program's success indicators, namely a 30% increase in knowledge in the Pekuwon Village community.